Building a successful school - Walsh, Mike. (London : Kogan Page, 1999)
The point of critical importance for all those in education is to be able to spot the signs of failure early enough to address them. Building a Successful School brings together a wealth of experience and practical advice from Mike Walsh, a Senior LEA inspector and officer with significant Ofsted inspection experience. By looking in detail at the elements involved in developing and managing schools, this book identifies where weakness and problems may occur, how failure manifests itself and how to turn those elements of failure around." "Written for senior teachers and managers, governors and local authority managers, this book will also make informed reading for parents and anyone with an interest in building and maintaining a successful school."--BOOK JACKET.
Keywords: School management and organization -- Great Britain; Educational change -- Great Britain